Alternative splicing responses to salt stress in Glycyrrhiza uralensis revealed by global profiling of transcriptome RNA-seq datasets - Yao, Hua; Li, Guozhi; Gao, Zhuanzhuan; Guo, Fei; Feng, Jianghua; Xiao, Guanghui; Shen, Haitao; Li, Hongbin (Frontiers in Genetics, 2024)
Excessive reactive oxygen species stress due to salinity poses a significant threat to the growth of Glycyrrhiza uralensis Fisch. To adapt to salt stress, G. uralensis engages in alternative splicing (AS) to generate a variety of proteins that help it withstand the effects of salt stress. While several studies have investigated the impact of alternative splicing on plants stress responses, the mechanisms by which AS interacts with transcriptional regulation to modulate the salt stress response in G. uralensis remain poorly understood. In this study, we utilized high-throughput RNA sequencing data to perform a comprehensive analysis of AS events at various time points in G. uralensis under salt stress, with exon skipping (SE) being the predominant AS type. KEGG enrichment analysis was performed on the different splicing genes (DSG), and pathways associated with AS were significantly enriched, including RNA transport, mRNA surveillance, and spliceosome. This indicated splicing regulation of genes, resulting in AS events under salt stress conditions. Moreover, plant response to salt stress pathways were also enriched, such as mitogen-activated protein kinase signaling pathway – plant, flavonoid biosynthesis, and oxidative phosphorylation. We focused on four differentially significant genes in the MAPK pathway by AS and qRT-PCR analysis. The alternative splicing type of MPK4 and SnRK2 was skipped exon (SE). ETR2 and RbohD were retained intron (RI) and alternative 5’splice site (A5SS), respectively. The expression levels of isoform1 of these four genes displayed different but significant increases in different tissue sites and salt stress treatment times. These findings suggest that MPK4, SnRK2, ETR2, and RbohD in G. uralensis activate the expression of isoform1, leading to the production of more isoform1 protein and thereby enhancing resistance to salt stress. These findings suggest that salt-responsive AS directly and indirectly governs G. uralensis salt response. Further investigations into AS function and mechanism during abiotic stresses may offer novel references for bolstering plant stress tolerance.